Perkembangan Pasar Alai Di Kota Padang (2000-2020) - Dhika Halya; Etmi Hardi (Jurusan Sejarah FIS UNP, 2022)
The market is a meeting place for buyers and traders to carry out transactions and the goods and services contained there. Meanwhile, in an abstract sense, the market can be interpreted as a meeting place for sellers and buyers to make bid transactions. Alai Market is a traditional market where sellers and buyers can bargain directly. The goods traded are goods in the form of basic necessities. A structure that allows buyers and sellers to exchange goods, services and information. This study aims to describe the development of the Alai market in the 2000-2020 range and also to find out what policies have been issued by the local government to develop the potential of the Alai market in the 2000-2020 range. The researcher uses qualitative research methods with historical methods related to the process of tracing historical sources to produce historical facts and presenting them in the form of historical writing which is done by heuristics, source criticism and finally interpretation. The results of the study showed that market development depended on government policies that led at that time in 2020 the Padang city government managed to make improvements by processing waste, moving 6000 street vendors and building some infrastructure for the market.